Kewenangan Badan Pengawas Perdagangan Berjangka Komoditi Dalam Memberikan Perlindungan Hukum Bagi Korban Investasi Bodong Emas Digital : Studi Kasus PT Tamasia Global Sharia - Ario Andika Baskoro; Yudho Taruno Muryanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to determine the regulations related to the implementation of digital gold investment in Indonesia and to determine the form of legal protection that BAPPEBTI can provide through statutory regulations for digital gold customers. This research is normative legal research that is descriptive in nature. The research approach used is a statutory and conceptual approach. The types and sources of legal materials used consist of primary legal materials and secondary legal materials. The legal material collection technique used is literature study a. The legal material analysis technique used is deductive using the syllogism method. Based on the research results, it was found that the implementation of digital gold investment trading in Indonesia is generally regulated in the Commodity Futures Trading Law, explained in more detail in Minister of Trade Regulation No. 119 of 2018, and the technical provisions are regulated in BAPPEBTI Regulations. The legal protection that BAPPEBTI can provide to digital gold customers includes carrying out supervision and even inspection of companies carrying out digital gold trading activities, then if violations are found by the company concerned, BAPPEBTI can impose administrative or criminal sanctions. However, there is a contradiction in Article 6 letters e and f in the Commodity Futures Trading Law, in letter e it is stated that BAPPEBTI has the authority to carry out inspections of parties who have business permits, individual permits, approvals or registration certificates. However, in letter f it is stated that BAPPEBTI appoints another party to carry out certain inspections in the context of implementing BAPPEBTI's authority as referred to in letter e. This shows that BAPPEBTI as a special institution for futures trading cannot be directly involved in enforcing the futures trading system, which means that BAPPEBTI's role in providing legal protection for digital gold customers is not optimal.